2015
DOI: 10.1121/1.4913273
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and objective rating of spectrally different pseudorandom noises—Implications for speech masking design

Abstract: Artificial sound masking is increasingly used in open-plan offices to improve speech privacy and to reduce distraction caused by speech sounds. Most of the masking sounds are based on pseudorandom continuous noise filtered to a specific spectrum that should be optimized in respect with speech masking efficiency and comfort. The aim of this study was to increase basic understanding regarding the comfort. The second aim was to determine how well objective rating methods (15 different noise indices) predict the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 29 publications
1
27
1
Order By: Relevance
“…This is in line with the laboratory experiment of Haapakangas et al (2011) which showed that the type of masking sound had an effect on cognitive performance and acoustic satisfaction even though the A-weighted SPL was constant. Additionally, Hongisto et al (2015) found that the spectrum alone explained the acoustic satisfaction of pseudo-random noises. Our study supports the findings of these previous studies but we cannot say which is more important: the spectrum or the type of sound.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with the laboratory experiment of Haapakangas et al (2011) which showed that the type of masking sound had an effect on cognitive performance and acoustic satisfaction even though the A-weighted SPL was constant. Additionally, Hongisto et al (2015) found that the spectrum alone explained the acoustic satisfaction of pseudo-random noises. Our study supports the findings of these previous studies but we cannot say which is more important: the spectrum or the type of sound.…”
Section: Discussionmentioning
confidence: 99%
“…Such a sound masking spectrum has been investigated in field conditions by, e.g., Helenius and Hongisto (2004), Hongisto (2008) and Hongisto et al (2012). A laboratory study of Hongisto et al (2015) showed that the subjects preferred a pseudo-random noise with a slope of −7 dB per octave doubling to a slope of −5 dB per octave doubling. Their study showed that the spectrum is an important basic feature of sound masking that should be carefully reported when the perception of sound masking is investigated.…”
Section: Introductionmentioning
confidence: 99%
“…There are two potential reasons why these participants found the modified brown masking noise unpleasant. Firstly, the actual spectrum of the modified brown masking emitted by the earphones was distinctly different from brown masking noise used and found to be acceptable in previous studies (Hongisto, Oliva and Rekola 2015). On reflection masking noise such as those investigated by Haapakangas, Kankkunen, et al 2011 may have been more acceptable to the participants.…”
Section: Rejection Of Earphones Due To Masking Noise Level Type and mentioning
confidence: 73%
“…Noise with a spectrum of between -5dB per octave to -7dB per octave is considered to be close to brown noise (Hongisto, Oliva and Rekola, Subjective and objective rating of spectrally different psuedorandum noises -Implications for speech masking design 2015). A recent study has identified -7dB per octave as being an acceptable masking noise (Hongisto 2015). Of the eleven spectrally difference noises evaluated brown noise (-7dB per octave) resulted in the highest satisfaction.…”
Section: Sound Conditionsmentioning
confidence: 94%
“…Thereafter, the sound pressure levels L 2 in the receiving room could be calculated on the basis of level differences D. There are several noise ratings used in description of noise spectrum in a room [e.g. [25][26][27][28]. Our purpose was to find out how the SNQs for airborne sound insulation are associated with the levels of transmitted living sounds.…”
Section: Correlation Between Snqs and Transmitted Living Sound Levelsmentioning
confidence: 99%